Agama dan Budaya Ekonomi Kewirausahaan di Credit Union Bahtera Abadi Kabupaten Sragen - Gunawan Anggonosamekto (Universitas Negeri Medan, 2021)
The purpose of this study is to describe the religion and culture of entrepreneurship economics as a tool for public welfare. Socio-economic prosperity is always interwoven in the history of religious human life. This study uses qualitative research methods with descriptive analysis to see religion as part of economic culture to fight for entrepreneurial welfare as a joint empowerment movement for social welfare. But religion and economics need the skills to make it happen, so that not only talk about individual interests (self economic), but for living together (social economy). Religion in this case Christianity (the church) becomes the locus of economic empowerment through the Credit Union (CU) to realize prosperity in a community. The behavior of economic growth is indeed strongly influenced by the values that develop in a particular community. Considering that economic development cannot be separated from the cultural process itself. The practice of CU at CU Bahtera Abadi has provided a change in economic cultural behavior through awareness education and skills for members to develop their skills in managing themselves and themselves with other individuals. On the other hand, it contributes to the culture of organization and entrepreneurship. The values of education and empowerment are very important to continue to be developed to form a new habitus for future generations.